Ugly Feelings in Mariana Enriquez's Short Fiction. Issue 2 (7th February 2021) - Vázquez-Medina, Olivia
Abstract: This article explores the affective resonances of three stories from Mariana Enriquez's Las cosas que perdimos en el fuego (2016). Although fear is the predominant emotion evoked in Enriquez's brand of political horror, there is considerable depth and complexity to her stories, in terms of both the emotional content portrayed in them and the readerly solicitation staged through the narratives' formal and stylistic qualities. The synergies between fear, disgust, unease, guilt and other 'ugly feelings' result in an overall mood of disquietude that underlies the aesthetic and political potency of Enriquez's fiction.